TINJAUAN PENGGUNAAN APLIKASI FLIP UNTUK LAYANAN TRANSFER ANTAR BANK - Devita Ariyani, (2023)
This review of the use of the Flip application aims to determine the use value of the Flip application based on perceived ease of use, price value, perceived safety of use, perceived trust in use and motivation to use. The method used in this study refers to the quantitative method, the data collection used was obtained through questionnaires as the primary data source and analyzed using descriptive analysis methods. From the results of the research conducted, it proves that the majority of respondents know that the Flip application is recommended by their friends/relatives, the Flip application is able to provide ease of use because the Flip application can be accessed anywhere and anytime, provides cost savings due to free interbank transfer administration fees and lots of promos. attractive, and also provides a sense of security to its users because of the helpful customer service, the flip application is also able to provide a sense of trust because the flip application has been licensed by Bank Indonesia. These perceptions present a motivation for using the Flip application so that Flip can be the main choice for them when they have to make interbank transfer transactions.